THE RHETORIC OF THE WAR THREAT: NATO – THE ONSLAUGHT OF THE EAST - D. S. Lapay (Вестник Кемеровского государственного университета, 2015)
The foreign policy changes led to changes in the military rhetoric. The most useful frames of modern military rhetoric NATO are: «Russian aggression», «military threat from Russia», «the war for justice», «war for democracy», «war for peace», «responsibility to the world», «sacred mission to the world». All these frames have already met in the world history as a Hitler`s frame «Drang nach Osten». This article deals with the description of these frames of NATO` modern military rhetoric.